The HPV Cellular Transactivator Brn-3a Can Be Used to Predict Cervical Adenocarcinoma and Squamous Carcinoma Precancer Lesions in the Developed and Developing Worlds - Daniel Ndisang; Felipe Lorenzato; Michael Sindos; Ashfaq Khan; Albert Singer; David S. Latchman (Obstetrics and Gynecology International)
The cellular transactivator Brn-3a has previously been shown to be expressed at elevated levels in the cervix of women with squamous cell carcinoma of the cervix (SCC) and to activate the expression of HPV E6 mRNA. In this study, we show that common and rare cervical precancer lesions, including those of adenocarcinoma (AC), which are usually difficult to diagnose using classical procedures, also expressed high levels of Brn-3a and can be diagnosed by measuring the levels of Brn-3a and E6 mRNAs.